KOLABORASI ORANG TUA DAN GURU DALAM MENINGKATKAN PROFESIONALITAS PENDIDIK PAUD - Omang Komarudin; Siti Aminah; Kamilatusalamah; Siti Badriah; Cindy Arsya Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Collaboration between parents and teachers is a strategic component in enhancing the professionalism of early childhood educators. In early childhood education, teacher professionalism is shaped not only by pedagogical competence but also by the ability to build partnerships with parents as the primary learning environment for children. This literature-based study analyzes various forms of parent–teacher collaboration and their contribution to improving teacher professionalism in early childhood education. The findings indicate that effective collaboration involves two-way communication, joint planning of learning activities, parent involvement in school programs, and the use of parental feedback to improve teacher capacity. Such synergy supports the development of pedagogical, social, personal, and professional competencies. The study concludes that partnership-oriented approaches rooted in trust, communication, and active participation are essential to improving PAUD educational quality.